Otoprotective Mechanisms of Carvone As An Antioxidant Agent Against Ototoxic Damage Caused By Paclitaxel - DİNCER, Büşra; ATALAY, Fatma; TATAR, Arzu (Marmara University, 2023)
Objective: Ototoxicity is cellular damage caused by the use of solid treatments as chemotherapeutics in critical illnesses like cancer. The generation of free radicals is linked to fluctuating hearing loss caused by chemotherapeutics. Antioxidants can help to prevent ototoxicity-related oxidative damage. Carvone (CVN) is a monoterpene with excellent antioxidant properties that protect against oxidative damage. This study investigates the biochemical and functional aspects of CVN’s putative otoprotective mechanisms against paclitaxel (PCX)-induced ototoxicity. Methods: 24 Wistar albino rats were assigned into four different groups: Control, CVN, PCX, and PCX+CVN. Once a week, the control group received saline. The PCX group received 5 mg/kg PCX intraperitoneally once a week (4 times). Once a week, the CVN group received 50 mg/kg intraperitoneally. The PCX+ CVN group received 5 mg/kg PCX followed by 5 mg/kg CVN once a week. All animals were subjected to deterioration product otoacoustic emission testing before (day 0) and after drug administration (day 23). Results: PCX showed an ototoxic effect by weakening otoacoustic emission values. PCX leads to significant otoacoustic emission value shifts ameliorated by CVN co-treatment (for 2000Hz p< .001, for 4000 levels p< .01, for 6000Hz p< .001, and for 8000 Hz p< .01 in PCX+CVN group). Furthermore, the PCX group had significantly greater malondialdehyde levels and significantly lower glutathione levels in the cochlear tissues, compared to the other groups. Co-administered CVN with PCX reversed these effects, making oxidative stress parameters close to those of the control group (for GSH levels p< .001, for MDA levels p< .01 in the PCX+CVN group). Conclusion: According to the findings, CVN appears to preserve cochlear function in rats against the disruptive effects of PCX.
Keywords: Temel Farmakoloji; Antioxidant; carvone; ototoxicity; oxidative stress; paclitaxel; Basic Pharmacology; 3. Good health